1999
DOI: 10.1093/jac/44.suppl_2.11
|View full text |Cite
|
Sign up to set email alerts
|

The socio-economic burden of influenza

Abstract: Influenza epidemics and pandemics have a huge impact on society and individuals. The weight and scope of the burden of influenza varies with the age and underlying health of the patient. The disease imposes a significant burden on all individuals, but hospitalization and treatment occur more frequently in high-risk patients (the elderly and those with certain underlying medical conditions); patient populations that are increasing in size. Escalating medical costs have increased the need to quantify the burden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
72
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(78 citation statements)
references
References 26 publications
1
72
0
5
Order By: Relevance
“…Other studies have found that vaccination the previous year and the belief that vaccination is effective have enhanced the uptake of influenza vaccination by healthcare workers. 4 ' 5 This is consistent with our experience of 71.8% of vaccinated staff indicating that they had been vaccinated the previous year. Favorable outcomes from the previous vaccination such as minimal discomfort at the time of injection, absence of influenza, reduced sick leave required to be taken, and confidence in the vaccinating staff contributed to the vaccination uptake.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…Other studies have found that vaccination the previous year and the belief that vaccination is effective have enhanced the uptake of influenza vaccination by healthcare workers. 4 ' 5 This is consistent with our experience of 71.8% of vaccinated staff indicating that they had been vaccinated the previous year. Favorable outcomes from the previous vaccination such as minimal discomfort at the time of injection, absence of influenza, reduced sick leave required to be taken, and confidence in the vaccinating staff contributed to the vaccination uptake.…”
supporting
confidence: 87%
“…When only high-risk staff are vaccinated, others can erroneously believe that they are not in a high-risk category and so do not participate in the vaccination program. 4 Offering vaccination to all staff can reduce the risk of staff who do not have contact with patients transmitting the influenza virus to staff who do have contact with patients while at work, in both clinical settings and dining room facilities. 4 Previously, the program was implemented primarily by the clinical nurse consultant for infection control, with assistance from the night duty coordinators and staff clinic.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12] In healthy adult populations, the main impact of influenza, which typically leads to 3 to 4 days of bed rest and restricted activity for several more days, is work absenteeism and productivity losses, which account for 80-90% of the total cost of the disease. 4,[12][13][14][15][16] Vaccination is the most effective way of reducing the large economic burden of influenza.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of the logistic regression analysis do not appear to support this possibility, although the findings are not conclusive (Table 2). Secondly, according to previous studies, it is widely recognized that, once infection with influenza has been established, serious complications are often observed among high-risk patients, such as those with chronic diseases, elderly patients, and children (3,4,14,16,26). In line with these findings, we found significant differences in the frequencies of medical testing and treatment between vaccinated and unvaccinated groups only among bed-bound in-patients, and demonstrated that bed-bound patients were at the highest risk for co-morbidity.…”
Section: Discussionmentioning
confidence: 99%